Peculiarities of diagnostics and treatment of chronic generalized periodontitis in patients with heart rhythm disorders taking anticoagulants - M. V. Lomakina; A. G. Volkov; V. M. Grinin; N. Zh. Dikopova; L. V. Abolyan; I. A. Nikolskaya (Эндодонтия Today, 2025)
INTRODUCTION. A clinical examination and treatment were conducted on 104 patients with cardiac arrhythmias who were receiving anticoagulant therapy. The patients were aged between 45 and 59 years (classified as middle age according to the WHO classification) and were diagnosed with moderate chronic generalized periodontitis (53% male, 47% female). AIM. To evaluate the effectiveness of standard therapeutic measures in the treatment of chronic generalized periodontitis in patients receiving anticoagulant therapy and to identify the specific characteristics of the disease course in this patient group. MATERIALS AND METHODS. The study included 104 patients with cardiac arrhythmias who were receiving anticoagulant therapy and were diagnosed with moderate chronic generalized periodontitis. Standard treatment for periodontitis was administered with consideration of anticoagulant use. Clinical parameters, including gingival bleeding, periodontal status, and the effectiveness of therapeutic measures, were assessed. CONCLUSIONS. Standard therapeutic measures for the treatment of chronic generalized periodontitis were equally effective in patients receiving and not receiving anticoagulant therapy. However, a distinguishing feature of periodontitis treatment in patients receiving anticoagulants was the persistence of high levels of gingival bleeding after the resolution of the inflammatory process in the periodontium, which was attributed to anticoagulant use. This situation often misleads clinicians, who may interpret gingival bleeding as a sign of inflammation, resulting in overdiagnosis and inflated values of corresponding indices. Standard therapeutic methods were found to be effective and sufficient for preventing the progression of pathological processes in the periodontium in this patient group.